Fitness Education Model to Improve Learning Achievement of PJOK Subjects: A Focus Senior High School Students - Anwar, Nur Indah Atifah; Hamzah, Alimin; Aksir, Muh. Ilham (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study aimed to assess the effectiveness of the Fitness Education Model in enhancing learning achievement in physical education, sports, and health subjects among students at public senior high schools. The study used a quasi-experimental method with a nonequivalent control group pretest-posttest design. Students from public senior high school 1 Polewali comprised the study's population, and the n-stage random sampling technique selected a sample of 50 students, including 30 males and 20 females. We collected data through observation and questionnaires. Data analysis used a t-test with a significance level of 5% to compare the results of the pretest and posttest. The results showed that the implementation of the Fitness Education Model was effective in improving student learning achievement compared to conventional methods. Students in the experimental group experienced an average increase in posttest scores of 17.5 points, compared to 9.5 points in the control group. Statistical tests showed a significant difference (p < 0.05) between the two groups. In addition, qualitative observations indicated that students in the experimental group were more active, motivated, and showed better social engagement than the control group. Therefore, we can conclude that the Fitness Education Model not only enhances students' motor and cognitive skills but also fosters the development of character traits like responsibility and cooperation.